1981
DOI: 10.1104/pp.68.3.727
|View full text |Cite
|
Sign up to set email alerts
|

RNA, Proteins and Polyamines During Tube Growth in Germinating Apple Pollen

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 17 publications
3
37
0
1
Order By: Relevance
“…Red Chief was collected from experimental plots (Dipartimento di Colture Arboree, Bologna, Italy; Azienda Agricola Rondinini, Faenza, Italy). Handling and storage were performed as described by Bagni et al [19].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Red Chief was collected from experimental plots (Dipartimento di Colture Arboree, Bologna, Italy; Azienda Agricola Rondinini, Faenza, Italy). Handling and storage were performed as described by Bagni et al [19].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Accumulating evidence has showed that endogenous polyamine is important for pollen germination and pollen tube growth 78,92 . Bagni et al 6 reported that biosynthesis of polyamines took place before pollen tube emergence. MGBG reduced (at low concentration) or inhibited (at high concentration) pollen germination, which was promoted by Spd at low concentration 64 .…”
mentioning
confidence: 99%
“…In those organs, Pas content has been shown to be related to the processes of cell proliferation, ovule differentiation, embryo sac formation, transcriptional and proteinlevel regulation during pollen-tube emergence and sexual differentiation (Bagni et al 1981;Biasi et al 1999;Song et al 2001). In the styles of 'Housui' Japanese pear (P. pyrifolia), an increase in Pas was observed 20 h after pollination, mainly owing to a significant putrescine increase after self-and cross-pollination; at the same time, an increase in ethylene production was reported (Franco-Mora et al 2005b).…”
Section: Introductionmentioning
confidence: 99%